Analisis Sistem Utilitas AC di Gedung General Library Berdasarkan Pedoman SNI - Atika Masruroh; Hanifatun Nabilah; Miftahul Khairi (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This study aims to determine whether the implemented system complies with recommended standards and to find opportunities for improvement in terms of energy efficiency and overall system performance. Therefore, it is expected that the results of this analysis will help design a more sustainable and efficient library building management. This study uses a descriptive quantitative research study method, namely research that emphasizes the collection of existing building data and analyzes the data in accordance with SNI guidelines on the AC Utility system. Quantitative is a form of research activity whose specifications are planned systematically and clearly structured from the beginning to the making of the research design. This research shows that: (1) The Use of AC Types in Buildings, (2) Air Conditioning in Buildings, (3) Mapping of AC Utilities in Buildings, (4) Data Analysis based on SNI Guidelines for AC Utilities. The results of this study show that almost all rooms in the General Library Building have AC requirements that exceed the standard. This will certainly cause swelling of electricity costs. Therefore, it is expected that the General Library Building will reduce the capacity of air conditioners in rooms that exceed the standard capacity and install air conditioners in rooms that have not been installed, so that the distribution of air conditioners will be more evenly distributed and all can feel the comfort.